2014
DOI: 10.1093/toxsci/kfu106
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in the Gene for Cytochrome P450 (CYP)1A1 Are More Susceptible Than Wild-Type to Hyperoxic Lung Injury: Evidence for Protective Role of CYP1A1 Against Oxidative Stress

Abstract: Hyperoxia contributes to acute lung injury in diseases such as acute respiratory distress syndrome in adults and bronchopulmonary dysplasia in premature infants. Cytochrome P450 (CYP)1A1 has been shown to modulate hyperoxic lung injury. The mechanistic role(s) of CYP1A1 in hyperoxic lung injury in vivo is not known. In this investigation, we hypothesized that Cyp1a1(-/-) mice would be more susceptible to hyperoxic lung injury than wild-type (WT) mice, and that the protective role of CYP1A1 is in part due to CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…FABP4 is one of fatty acid binding proteins, and the expression of FABP4 and FABP5 was enhanced during cirrhosis in hepatocarcinogenesis of rat model (Liu et al, 2009), which was not contradictory with our result and indicated an alteration of fat metabolism. One previous study showed that cytochrome P450 (CYP) 1A1 could protect lung from oxidative injury by decreasing levels of lipid hydroperoxides (Lingappan et al, 2014), and the Present study demonstrated that CYP1A1 was upregulated at three time points and activated fatty acid metabolism at 3 and 9 weeks, suggesting that CYP1A1 may also play a protective role by activating fatty acid metabolism in liver cirrhosis. According to the IPA analysis, LPS/IL-1-mediated inhibition of RXR function ranked first in the identified canonical pathways, and the study performed by Raghu et al (2012) indicated that this pathway was involved in ethanol metabolism in alcoholic fatty liver.…”
Section: Discussionmentioning
confidence: 51%
“…FABP4 is one of fatty acid binding proteins, and the expression of FABP4 and FABP5 was enhanced during cirrhosis in hepatocarcinogenesis of rat model (Liu et al, 2009), which was not contradictory with our result and indicated an alteration of fat metabolism. One previous study showed that cytochrome P450 (CYP) 1A1 could protect lung from oxidative injury by decreasing levels of lipid hydroperoxides (Lingappan et al, 2014), and the Present study demonstrated that CYP1A1 was upregulated at three time points and activated fatty acid metabolism at 3 and 9 weeks, suggesting that CYP1A1 may also play a protective role by activating fatty acid metabolism in liver cirrhosis. According to the IPA analysis, LPS/IL-1-mediated inhibition of RXR function ranked first in the identified canonical pathways, and the study performed by Raghu et al (2012) indicated that this pathway was involved in ethanol metabolism in alcoholic fatty liver.…”
Section: Discussionmentioning
confidence: 51%
“…Cytochrome P450 enzymes induction usually enhances detoxification; thus, induction is a protective mechanism. A protective role of Cyp1a1 has been described in the lung, where elevation of Cyp1a1 decreased oxidative stress in this tissue and decreased MDA and 4-HNE, the most prominent end-products of lipid peroxidation [34]. We believe that Cyp1a1 elevation is a compensatory response by keratinocytes to combat lipid peroxidation when Ubiad1 is silenced, and may reveal the importance of Ubiad1 in keratinocyte physiology.…”
Section: Discussionmentioning
confidence: 61%
“…Damaged animals were likely to be experiencing oxidative stress for two reasons: increased aerobic respiration and the macrophages oxidative burst during immune response. STRING identified changes in the cytochrome P450 system, which is known to be involved in mediating oxidative stress (Lingappan et al, 2014). In addition, the full NCBI nr annotation of the differentially expressed transcripts (Supplementary Table 2) included Thioredoxin, which is involved in cellular redox homeostasis (Jones and Go, 2010).…”
Section: Month After Damagementioning
confidence: 99%